Ensuring sustainability in forestry : certification of forests - Gupta, H. S. (Forester); Yadav, M.; Sharma, Dvijendra Kumar; Singh, A. M.; Energy and Resources Institute (New Delhi : The Energy and Resources Institute, 2013)
With reference to India.
Includes bibliographical references (pages 231-244).
Keywords: Sustainable forestry -- India; Forests and forestry -- India